2022
DOI: 10.1093/ajcn/nqac199
|View full text |Cite
|
Sign up to set email alerts
|

Healthy dietary patterns and risk of cardiovascular disease in US Hispanics/Latinos: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: Background Multiple dietary patterns haven been recommended by 2015–2020 Dietary Guidelines for Americans for the prevention of cardiovascular disease (CVD). The adherence to these patterns and its relationship with risk of CVD remain unclear in the US Hispanic/Latino population. Objectives We aimed to evaluate three healthy eating patterns measured by three dietary pattern scores (the Alternate Mediterranean diet (aMED), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Our findings are generally in line with those from previous US studies on hPDI and uPDI in relation to myocardial infarction, ischemic stroke, CVD mortality, and total mortality . Importantly, we observed that inverse associations between the hPDI and CVD end points (total CVD, myocardial infarction, and stroke) were independent of genetic disease risk.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are generally in line with those from previous US studies on hPDI and uPDI in relation to myocardial infarction, ischemic stroke, CVD mortality, and total mortality . Importantly, we observed that inverse associations between the hPDI and CVD end points (total CVD, myocardial infarction, and stroke) were independent of genetic disease risk.…”
Section: Discussionsupporting
confidence: 92%
“…Bu çalışmada enerjiden bağımsız olarak besin tüketimine dayalı bütüncül bir yaklaşım içerisinde geliştirilmiş diyet kalite indeksleri ile "fast food" tüketimi arasındaki ilişki incelenmiştir. Yapılan bazı araştırmalarda, en fazla tercih edilen ve farklı hesaplama algoritmasına ve yönlere sahip olan PREDIMED ve HEI-2015'e yüksek bağlılık olumlu sağlık ile ilişkilendirilmiştir (33,34). Yapılan kesitsel bir araştırmada, "fast food" tüketmeyen katılımcıların tüketen- (23).…”
Section: Bulgularunclassified
“…Studies have found that a good dietary pattern could reduce the incidence and mortality of CVD, diabetes, hypertension and other chronic diseases [7,8], and most diet-related deaths were caused by CVD, T2D and cancer [9]. Good dietary pattern has become the basis for the current treatment of CVD, as well as an extremely important link in the primary prevention of this disease [10].…”
Section: Introductionmentioning
confidence: 99%